The TEORI RETORIKA DARI KLASIK KE ALGORITMIK: KAJIAN LITERATUR TENTANG RETORIKA DAN KECERDASAN ARTIFISIAL - Putra, Perdana Maulana; Harry Yassir Elhadidy Siregar; Irwansyah (Universitas Riau, 2025)
The advancement of artificial intelligence (AI) is reshaping how humans interpret communication, challenging the boundaries of classical human-centered rhetorical theory. This study examines 30 Scopus-indexed publications from 2018–2025, tracing the evolution of rhetorical thought from humanistic traditions to algorithmic paradigms. It explores how Aristotle’s four core pillars; techné, ethos, pathos, and logos, are being redefined in AI-mediated communication. Using a Systematic Literature Review (SLR) guided by the PRISMA 2020 Extended Checklist and bibliometric mapping via VOSviewer, the analysis identifies six main thematic directions: rhetoric as techné, synthetic ethos, digital rhetorical literacy and ethical responsibility, algorithmic persuasion and non-human agency, public discourse formation through digital media politics, and applications in education, business, and health communication. Findings indicate that Aristotelian rhetoric remains relevant in the AI era but requires dynamic theoretical adaptation to human-algorithm interactions. The study proposes an algorithmic rhetoric framework integrating ethical, technological, and epistemological dimensions to understand persuasion in digital communication. Practically, it emphasizes the development of AI-based rhetorical literacy to ensure digital persuasion practices remain transparent, ethical, and human-centered. Keywords: Rhetoric, Artificial Intelligence, Persuasion, Algorithmic Rhetoric